Ekranisasi sebagai Media Pembelajaran Literasi Sastra: Analisis Proses Adaptasi Pembuatan Drama Pendek Berbasis Cerpen - Anis Setyawati; Rifa Suci Wulandari (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study explores the idea of ekranisasi, or screen adaptation, as an educational approach to enhance literary literacy, particularly through the transformation of short stories into succinct dramatic performances. Students participate in an experiential literary literacy approach as actors, writers, and readers. Three adaptation parameters, decrease, addition, and variation that are frequently seen inside the ekranisasi process are the subject matter of this research. According to the research findings, the process of screen adaptation significantly boosts students' understanding of the narrative components found in short tales while also encouraging the development of creative abilities to interpret and an admiration for literary aesthetics. collaborative, integrative, and contextually appropriate teaching method. As a result, ekranisasi can be described a short stories and multifaceted method of teaching literary literacy combining textual comprehension and artistic achievement in the teaching of contemporary literature.